2022
DOI: 10.1111/apt.17092
|View full text |Cite
|
Sign up to set email alerts
|

Children included in randomised controlled trials of biologics in inflammatory bowel diseases do not represent the real‐world patient mix

Abstract: Summary Background Patients enrolled in randomised controlled trials (RCTs) may differ from the target population due to restricted eligibility criteria. Aim To compare treatment response to biologics in routine practice for children with inflammatory bowel diseases (IBD) who would and would not have been eligible for enrolment in the regulatory RCT of the same drug. Methods We enrolled children with IBD who initiated adalimumab, infliximab, vedolizumab or ustekinumab. The eligibility criteria as defined in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 19 publications
(45 reference statements)
0
6
0
Order By: Relevance
“…Patients who developed ATIs were considered non-responders, and showed high serum levels of CRP and 90K. Several studies in recent years have shown a correlation between high serum CRP levels and a loss of response to anti-TNF treatment [ 20 , 32 , 33 , 34 , 35 ]. Interestingly, we found that non-responder patients showed higher 90K serum levels at baseline than responders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients who developed ATIs were considered non-responders, and showed high serum levels of CRP and 90K. Several studies in recent years have shown a correlation between high serum CRP levels and a loss of response to anti-TNF treatment [ 20 , 32 , 33 , 34 , 35 ]. Interestingly, we found that non-responder patients showed higher 90K serum levels at baseline than responders.…”
Section: Discussionmentioning
confidence: 99%
“…C-reactive protein (CRP) is the most common serum biomarker of inflammation in IBD, and its characteristics are useful for grading inflammation, monitoring the response to therapy, and to identify recurrent inflammation after medically or surgically induced remission [ 20 , 32 ]. Recent studies associated CRP levels with biomarkers and clinical disease activity indices in IBD patients [ 33 , 34 , 35 , 36 , 37 ]. In two distinct cohorts of pediatric IBD patients, an elevated CRP level was considered a risk factor for biologics treatment [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Although index studies in pediatric IBD have reported a lower primary nonresponse rate, recent data have shown this is likely due to more stringent inclusion criteria in clinical trials compared with the use of these drugs in realworld patients. 5 A common cause of pharmacokinetic loss of response is the formation of antibodies to IFX (ATIs), which is associated with lower trough levels and the occurrence of infusion reactions. 6 Immunogenicity-related factors include IFX therapy without a concomitant immunomodulator (IM), [7][8][9][10] suboptimal drug concentrations, 4 and carriage of the HLA-DQA1*05 allele.…”
Section: Introductionmentioning
confidence: 99%
“…However, primary nonresponse affects up to 40% of adults with IBD, while secondary nonresponse occurs in 20%–37% 3,4 . Although index studies in pediatric IBD have reported a lower primary nonresponse rate, recent data have shown this is likely due to more stringent inclusion criteria in clinical trials compared with the use of these drugs in real‐world patients 5 . A common cause of pharmacokinetic loss of response is the formation of antibodies to IFX (ATIs), which is associated with lower trough levels and the occurrence of infusion reactions 6 .…”
Section: Introductionmentioning
confidence: 99%